Non‐traumatic hemorrhagic myelopathy in dogs - Natalie West; Sarah Butterfield; Clare Rusbridge; Ana Fernandez; Joana Tabanez; Nichola Jane Rudolf; Simon Archer; Danielle Whittaker (Journal of Veterinary Internal Medicine, 2023)
Abstract Background Non‐traumatic spinal cord hemorrhage (NTSH) is an uncommon cause of myelopathy in dogs. Objectives Describe the clinical characteristics, concurrent medical conditions and underlying causes, magnetic resonance imaging (MRI) findings and outcome in dogs with NTSH. Animals Dogs diagnosed with NTSH using gradient echo T2‐weighted (GRE) sequences with or without histopathological confirmation of hemorrhage were included. Dogs with a traumatic cause were excluded, including those with compressive intervertebral disc extrusion. Methods Retrospective descriptive study; the databases of 2 referral hospitals were searched between 2013 and 2021. Results Twenty‐three dogs met inclusion criteria. The onset of signs was acute and progressive in 70% of cases; spinal hyperesthesia was variable (48%). Hemorrhage was identified in the thoracolumbar spinal segments in 65% of dogs. An underlying cause was identified in 65% of cases. Angiostrongylus vasorum represented 18% of the total cohort, followed by steroid‐responsive meningitis arteritis (SRMA; 13%). Overall, 64% of dogs had a good or excellent outcome, regardless of cause; which was increased to 100% for SRMA, 75% for A. vasorum and 75% for idiopathic NTSH. Outcome was not associated with neurological severity. Recovery rate was 67% and 50% for nociception‐intact and nociception‐negative dogs, respectively. Conclusions Larger prospective studies would be required to define prognostic factors for dogs with NTSH, but outcome appeared to be most influenced by the underlying cause, as opposed to neurological severity at presentation.